Analisis Layanan Perpustakaan Menggunakan Aplikasi iCilegon - Putri, Assyfa Ayu; Kesuma, Mezan el-Khaeri; Romlah, Romlah; You, Yawal (Jurnal El-Pustaka, 2023)
Library services are activities to meet the information needs of library users, in a fast, precise, and accurate manner. Based on the results of this study, it was stated that this research was descriptive with a quantitative approach. Data collection techniques were carried out by observing, documenting, interviewing, questionnaires, and studying the literature. This sampling technique is used if the total population is above 1000, thus taking a sample of at least 10% or equal to 10% so that the sample in the study is 117 out of 1172 populations. The results of the data analysis show that the information system at the library using the iCilegon application can run well, this is proven by obtaining 81.5% on system quality, 79.2% on information quality, 81.4% on service quality, 80.6% on usage, user satisfaction which has a total score of 79.6%, and 81.7% in net benefits. Thus this study argues that the implementation of using the iCilegon application can improve the quality of library services at the Cilegon City Library and Archives Service.